Immunostimulatory and anti-inflammatory impact of Fragaria ananassa methanol extract in a rat model of cadmium chloride-induced pulmonary toxicity - Nofal, Amany E.; AboShabaan, Hind S.; Fayyad, Reda M.; Ereba, Rafik E.; Omar, Nassar A.; Elsharkawy, Sherin M.; Elberri, Aya I. (Frontiers in Immunology, 2023)
Cadmium is an extremely dangerous heavy metal that can lead to disastrous consequences in all organisms. Several natural remedies reduce the toxicities of experimentally generated metals in animals. Strawberry contains several bioactive compounds that may mitigate heavy-metal toxicity. The study aim was to evaluate the ability of a strawberry fruit methanol extract (SE) to reduce Cd toxicity and to identify and quantify the active constituents of SE. Forty Wistar rats were classified into four groups: the control group– 1 ml saline IP; SE group– 100 mg of SE/kg rats orally; cadmium (Cd) group–2 mg CdCl2 /kg body weight/ IP daily; and treated group– SE given 1 hour before Cd administration. Administration of Cd induced several histopathological and immunohistochemical alterations in lung sections. Biochemical analysis of lung homogenates and mRNA levels of antioxidants and inflammatory cytokines indicated significant changes to the risk profile. SE administration significantly decreased the oxidative stress, inflammation, tissue damage, the mean area percentage of collagen fibers, and positive immuno-expressions of TNF-α and NF-κB induced by CdCl2. Moreover, the MDA, TNF-α, GM-CSF, and IL-1β levels in Cd-exposed rat lung tissue were significantly lower in the SE-treated group than in the Cd-group. SE significantly augmented lung GSH, SOD, HO‐1, GPx-2, and Nrf2 levels in Cd-exposed rats. SE mitigated Cd-caused oxidative stress and lung inflammation. Therefore, regularly consuming a strawberry-rich diet could benefit general health and help prevent and treat diseases.